Wodel-Edu: A tool for the generation and evaluation of diagram-based exercises - Gómez-Abajo, Pablo; Guerra, Esther; de Lara, Juan (Science of computer programming, 2023)
Creating and grading exercises are recurring tasks within higher education. When these exercises are based on diagrams – like logic circuits, automata or class diagrams – we can represent them as models, and use model-driven engineering techniques for the large-scale generation of quizzes, which can be automatically graded. This way, we propose a domain-independent tool for the generation and automated evaluation of diagram-based exercises called Wodel-Edu. Wodel-Edu is built atop Wodel, an extensible tool for model mutation, and offers seven kinds of diagram exercises. It supports code generation from the exercises for the Moodle platform, the web, Android and iOS applications. Evaluations from the professor and student perspectives show good results. •Our solution, Wodel-Edu, automates the generation and evaluation of online exercises.•Wodel-Edu supports seven kinds of domain-independent diagram-based exercises.•The system synthesizes exercises for the Moodle platform, the web, Android and iOS applications.